A Transformational Model of Legal-Claiming - Goldman, B. M. (Institutional Knowledge at Singapore Management University, 2009)
This paper proposes a model of legal-claiming based on the transformational approach to disputes detailed by Felstiner et al. The model suggest disputes evolve, with a number of areas of organizational behavior providing explanations for individual disputant actions at specific points in time, including self-categorization theory, attribution theory, social accounts, organizational justice, conflict escalation, and social information processing. Multiple propositions relating to legal-claiming were also developed that were inductively derived from in-depth interviews with 38 employees who filed employment-discrimination claims with the federal Equal Employment Opportunity Commission. Propositions focus on various stages of the dispute, including naming, blaming, claiming, and disputing. Important theoretical and practical implications and limitations of the transformational model proposed are discussed.